Assessment of Toxicity and Beneficiary Effects of Garcinia pedunculata on the Hematological, Biochemical, and Histological Homeostasis in Rats - Paul, Sudip; Ali, Md. Yousuf; Rumpa, Nur-E-Noushin; Tanvir, E. M.; Hossen, Md. Sakib; Saha, Moumoni; Bhoumik, Nikhil Chandra; Siew, Hua Gan; Khalil, Md. Ibrahim (Hindawi Publishing Corporation [Commercial Publisher], 2017)
This study was undertaken to investigate the toxicological profile of a methanolic extract of Garcinia pedunculata fruit in rats by conducting hematological, biochemical, and histopathological examinations. Long Evans rats were divided into four groups, each with 6 animals, and were treated with three oral doses (250, 500, and 1000mg/kg) once daily for 21 days.The extract did not cause significant changes in body and relative organweight, percentwater content, or hematological parameters at any administered doses. However, a significant dose-dependent positive effect in serum lipid profile and all atherogenic indices including the cardiac risk ratio, Castelli’s risk index-2, and the atherogenic coefficient were observed. Significant increases in the levels of iron and decreases in serumalkaline phosphatase, alanine transaminase, and lactate dehydrogenase activities and the levels of serum glucose were noted when the extract was administered at the highest dose (1000mg/kg). Histopathological examination of the target tissues further confirmed that the extract was safe and had no observed toxicological features. Our study indicates that G. pedunculata fruit is nontoxic, has the potential to be effective against atherosclerosis, and may be used as a hepatoprotectant.The fruit extract is also beneficial to those with iron deficiency and hyperglycemia.